Age-Related Alterations in Gait Function in Freely Moving Male C57BL/6 Mice: Translational Relevance of Decreased Cadence and Increased Gait Variability. (1st November 2018) - Tarantini, Stefano; Yabluchanskiy, Andriy; Fülöp, Gábor A; Kiss, Tamas; Perz, Aleksandra; O'Connor, Daniel; Johnson, Emily; Sorond, Farzaneh; Ungvari, Zoltan I; Csiszar, Anna
Abstract: Age-related gait dysfunction and balance disorders are a major cause of falls and injury in the elderly population. Epidemiological studies have shown that disturbances in gait coordination which manifest with age are associated with increased morbidity and mortality, impaired cognitive capacity, as well as reduced level of function and loss of independence. In geroscience, mice are the most frequently used model system to test efficiency of antiaging interventions. Despite the clinical importance of age-related gait abnormalities in older adults, the impact of aging on mouse gait coordination is not well documented in the literature. To characterize the effect of aging on mouse gait, we assessed gait function in young (3-month-old) and aged (24-month-old) freely moving C57BL/6 mice using the semiautomated, highly sensitive CatWalk XT system for quantitative assessment of footfall and motor performance. We found that aged mice exhibited significantly decreased cadence and increased stride time variability. Aging also tended to alter footfall patterns. In aged mice, speed, swing speed, stride length, duty cycle, base of support, terminal dual stance, the regularity index, and the gait symmetry index were unaltered. Thus, aging is associated with characteristic alterations in gait function in C57BL/6 mice, which could potentially be assessed as clinically relevant endpoints in geroscience studies testing the effects of antiaging interventions.